Partisipasi Masyarakat Memoderasi Pengaruh PAD, Dana Perimbangan, dan Belanja Modal Pada Kinerja Keuangan - Yunita, Putu Venny; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 30 No 4 (2020), 2020)
The research aims to analyze the influence of local government revenue, fiscal balance funds, and capital expenditures on the financial performance of local governments with community participation as a moderating variable. The population in this study were all regency and city governments in Bali Province consisting of 8 regencies and 1 city with a period of 5 years from 2014 to 2018. The total population in this study was 45. The sample technique used was the saturated sample the analysis technique used is Moderated Regression Analysis (MRA). The results of the study showed that the local government revenue and capital expenditure had a positive effect on the financial performance of the regional government, while the fiscal balance fund had no effect on the financial performance of the regional government. Community participation strengthens the influence of local revenue, balance funds and capital expenditure on the financial performance of local governments. Keywords : Local Government Revenue; Fiscal Balance Fund; Capital Expenditure; Community Participation; Financial Performance.